The research writer curiosity, discovery, dialogue - Van Rys, John; Meyer, Verne; Sebranek, Patrick (Wadsworth, 2012)
Helps students transition from writing 'the research paper' to doing research writing, from reporting information to working with ideas. This handbook helps students learn the research and writing skills needed for research projects and also enables them to apply and transfer these skills to their own disciplines.